Value of Ivabradine in Patients with Anterior ST-Elevation Myocardial Infarction: The VIVA-STEMI Study - Rezq, Ahmed; Saad, Marwan; Mahmoudy, Ahmed Al; Nozahi, Mostafa El (Cardiology and Cardiovascular Medicine, 2020)
Background: Role of ivabradine in patients with anterior wall ST-elevation myocardial infarction (STEMI) is unknown. Methods: This is a two-center, randomized controlled, double-blinded trial, that included patients presenting with anterior wall STEMI and eligible for primary percutaneous coronary intervention (PPCI) from June 2016 through July 2018. After PPCI, patients were randomized (1:1) to receive bisoprolol plus ivabradine (ivabradine group) versus bisoprolol plus placebo (control group). Up-titration of ivabradine and/or bisoprolol was performed over a period of 6 weeks in all patients as tolerated. The primary outcome was resting heart rate at 6 weeks. Other secondary clinical outcomes were studied. Results: A total of 670 patients were included. Ivabradine was associated with a significant reduction in heart rate compared to placebo at 2 weeks (73.0 ± 2.8 vs 78.2 ± 1.75 bpm, respectively, p<0.001), 4 weeks (67.1 ± 2.9 vs 73.3 ± 2.2 bpm, respectively, p<0.001), and 6 weeks (62.3 ± 2.1 vs 66.9 ± 2.9 bpm respectively, p=0.001). At 6 months, post-MI angina occurred in 30 (10.7%) versus 50 patients (17.6%) in ivabradine and control groups, respectively (p=0.022). Heart Failure (HF) hospitalizations were less in ivabradine group (14.6% versus 23.2%, p=0.010). At 12 months, there was a significant reduction in post-MI angina, and HF hospitalizations (16.7% versus 27.4%, p=0.002 and 21.7% versus 34.8%, p=0.001, in ivabradine and control groups, respectively). Conclusions: Ivabradine, in addition to beta-blocker therapy, in patients with anterior STEMI was associated with superior heart rate control and clinical outcomes compared to placebo. Larger randomized controlled trials are encouraged to confirm role of ivabradine in these patients.